Primary synovial chondromatosis of the talonavicular joint: A case report. Issue 4 (December 2016) - Kim, Jun-Beom; Song, In-Soo; Shin, Sang-Yeop; Yoon, Ja-Yeong
Highlights: Synovial chondromatosis is a benign synovial tumor with multiple cartilaginous nodules. It is most commonly found in large joints, such as the knee, hip, and shoulder. Occurrence in the foot and ankle is uncommon, especially in the talonavicular joint. However, it should be considered as a potential differential diagnosis of a juxtaarticular mass with mineralization, in the foot. Abstract: Synovial chondromatosis developes by metaplasia of the synovial cells in the synovium of joints, and is a benign synovial tumor with multiple cartilaginous nodules. It is most commonly found in single and large joints, such as the knee, hip, and shoulder. Occurrence in the foot and ankle is uncommon, although there have been previous reports in the orthopedic and radiological literature of primary synovial chondromatosis in the subtalr, calcaneocuboid, naviculocuneiform, and metatarsaophalangeal joints. To our knowledge, occurrence in the talonavicular joint is even rarer, with only one report in the literature to date. Here, we report a case of synovial chondromatosis of the talonavicular joint, alongside a review of the literature.